2013
DOI: 10.1364/oe.21.020544
|View full text |Cite
|
Sign up to set email alerts
|

Shaping of light beams along curves in three dimensions

Abstract: We present a method for efficient and versatile generation of beams whose intensity and phase are prescribed along arbitrary 3D curves. It comprises a non-iterative beam shaping technique that does not require solving inversion problems of light propagation. The generated beams have diffraction-limited focusing with high intensity and controlled phase gradients useful for applications such as laser micro-machining and optical trapping. Its performance and feasibility are experimentally demonstrated on several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
100
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(100 citation statements)
references
References 19 publications
(25 reference statements)
0
100
0
Order By: Relevance
“…Furthermore, optical beams that are governed by a swallowtail catastrophe were observed in [48]. Using a different approach that does not rely on the use of caustics or of an extended focus, paraxial shaping of light in three-dimensions is presented by superimposing multiple Gaussian beams along an arbitrary curve [49].…”
Section: Other Classes Of Paraxial Accelerating Wavesmentioning
confidence: 99%
“…Furthermore, optical beams that are governed by a swallowtail catastrophe were observed in [48]. Using a different approach that does not rely on the use of caustics or of an extended focus, paraxial shaping of light in three-dimensions is presented by superimposing multiple Gaussian beams along an arbitrary curve [49].…”
Section: Other Classes Of Paraxial Accelerating Wavesmentioning
confidence: 99%
“…Roichman et al proved that an optical line trap with uniform intensity and gradient phase can transfer particles along the optical line automatically owing to the optical forces arising from the phase gradient of the beam [10]. Since control of both the amplitude and phase of an optical beam is important for many applications, researchers proposed various algorithms to beam shape the complex amplitude of an arbitrary optical beam [11][12][13][14][15][16][17]. For example, non-iterative algorithms were proposed to generate a beam whose intensity and phase were prescribed along arbitrary 3D curves [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Since control of both the amplitude and phase of an optical beam is important for many applications, researchers proposed various algorithms to beam shape the complex amplitude of an arbitrary optical beam [11][12][13][14][15][16][17]. For example, non-iterative algorithms were proposed to generate a beam whose intensity and phase were prescribed along arbitrary 3D curves [12,13]. Rigorous approaches were also proposed to directly calculate phase-only distributions of DOEs for beam shaping of complex-amplitudes of output beams [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the generated self‐accelerating vortex beam follows the predesigned parabolic trajectory and exhibits the diffraction‐free behaviors. Unlike the traditional self‐accelerating beam with only one main lobe along the predesigned trajectory, this self‐accelerating vortex beam has the doughnut‐like vortex core moving along the trajectory. Figure c is the transverse intensity profiles at four different propagation distances of z = 30 µm (p1), z = 60 µm (p2), z = 140 µm (p3), and z = 170 µm (p4) for the self‐acceleration TC inversion beam with parabolic trajectory.…”
Section: Resultsmentioning
confidence: 99%